Impact of Economic Progress, Energy Consumption and Carbon Dioxide Emissions on Life Expectancy: Evidence from Asia and Africa (Journal of Social Sciences Review, 2022)
In today's society, determining living standards requires taking into account life expectancy. Thus, a key concern for policymakers is the analysis of life expectancy characteristics. The life expectancy is evaluated using the panel quantile regression model across many quantile ranges, including 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 0.95. From 2000 through 2018, the study examines the effects of economic progress, energy use, and carbon dioxide releases on life expectancy across Asia and Africa. The analysis shows that CO2 emanations and life expectancy are intimately linked across all life expectancy quantiles. The impact of economic progress on life expectancy is negative in all except 0.95 quantiles. Additionally, except for the higher quantile (0.95), there is a negative and significant correspondence between hydroelectricity usage and life expectancy in the low and higher quantile series. The findings have thus shown beneficial impacts on life expectancy in low, medium, and greater quantities of petroleum and other liquid consumption. The outcomes suggest boosting the corporate structure to increase productivity and development. However, implementing a clean form of energy sources, i.e., renewable energy and technological efforts, need to employ excellently, contributing to environmental sustainability and a healthy ecosystem.
Keywords: Economic Progress; Life Expectancy; Carbon Dioxide Emissions; Renewable & Non-Renewable Energy; Quantile Regression Model